Sodium butyrate is incorporated into central metabolism in fly head while inducing oxygen consumption increase. - Annika Müller-Eigner; Benedikt Gille; Frederik Dethloff; Chen Meng; Christina Ludwig; John T Heiker; Patrick Giavalisco; Shahaf Peleg (PLoS ONE)
Butyrate has been proposed as a drug therapy by acting as a lysine deacetylase (KDAC) inhibitor and elevating protein acetylation, in particular on histones. Nonetheless, recent studies suggest that tissues such as the gut can utilize butyrate as a metabolite. We have previously shown that the addition of butyrate induces a rapid increase of oxygen consumption in whole Drosophila melanogaster heads. Here we show that while head oxygen consumption is increased by the addition of butyrate, no apparent changes are observed on the proteome and acetylome. Instead, we show that butyrate is metabolized and incorporated into the tricarboxylic acid (TCA) cycle. Collectively our data supports the notion that the therapeutic benefits of acute butyrate treatment may be also mediated by improving metabolic rates, rather than solely targeting the epigenome or acetylome.